How the viewing of familiar landscapes prior to release allows pigeons to home faster: evidence from GPS tracking. - Biro, D; Guilford, T; Dell'Omo, G; Lipp, H (2002)
Providing homing pigeons with a 5 min preview of the landscape at familiar sites prior to release reliably improves the birds' subsequent homing speeds. This phenomenon has been taken to suggest that the visual panorama is involved in familiar-site recognition, yet the exact nature of the improvement has never been elucidated. We employed newly developed miniature Global Positioning System (GPS) tracking technology to investigate how access to visual cues prior to release affects pigeons' flight along the length of the homing route. By applying a variety of novel analytical techniques enabled by the high-resolution GPS data (track efficiency, virtual vanishing bearings, orientation threshold), we localised the preview effect to the first 1000 m of the journey. Birds denied preview of a familiar landscape for 5 min before take-off flew an initially more tortuous path, including a high incidence of circling, possibly as part of an information-gathering strategy to determine their position. Beyond the first 1000 m, no differences were found in the performance of birds with or without preview. That the effect of the visual treatment was evident only in the early part of the journey suggests that lack of access to visual cues prior to release does not result in a non-specific effect on behaviour that is maintained throughout the flight. Instead, it seems that at least some decisions regarding the direction of home can be made prior to release and that such decisions are delayed if visual access to the landscape is denied. Overall, the variety of approaches applied here clearly highlight the potential for future applications of GPS tracking technology in navigation studies.